Emperors and Political Culture in Cassius Dio's Roman History - Davenport, Caillan; Mallan, Christopher (Cambridge University Press, 2021)
The Roman History of Cassius Dio provides one of the most important continuous narratives of the early Roman empire, spanning the inception of the Principate under Augustus to the turbulent years of the Severan Dynasty. It has been a major influence on how scholars have thought about Roman imperial history, from the Byzantine period down to the present day, as well as being a work of considerable literary sophistication and merit. This book, the product of an international collaborative project, brings together thirteen chapters written by scholars based in Europe, North America, and Australia. They offer new approaches to Dio's representation of Roman emperors, their courtiers, and key political constituencies such as the army and the people, as well as the literary techniques he uses to illuminate his narrative, from speeches to wonder narratives.